Dolores [videorecording (DVD)] - Bratt, Peter, 1962-; Clinton, Hillary Rodham; Davis, Angela Y. (Angela Yvonne), 1944-; Huerta, Dolores, 1930- ([publisher not identified], 2018)
Chronicles the life of Dolores Huerta, an American labor and civil rights activist.